The genus Leptoxyphium (Capnodiaceae) from China - Yang, Hui; Ariyawansa, Hiran A.; Wu, Hai-Xia; Hyde, Kevin D. (Phytotaxa, 2014)
Leptoxyphium is a relatively poorly known genus of sooty moulds in Capnodiaceae (Dothideomycetes). This paper introduces one new species of Leptoxyphium, L. glochidion and the first record of L. kurandae for China. L. glochidion is introduced as a new species based on morphology and molecular data and is compared with related taxa. Descriptions, illustrations and notes are provided for the two species, which are analyzed by ITS, LSU and SSU sequence data. The phylogenetic analysis shows that the two species cluster in Leptoxyphium (Capnodiaceae). L. glochidion separates from other species of the genus, while L. kurandae clustered with the type strain